BriXS, a new X-ray inverse Compton source for medical applications. (September 2020) - Cardarelli, P.; Bacci, A.; Calandrino, R.; Canella, F.; Castriconi, R.; Cialdi, S.; Del Vecchio, A.; di Franco, F.; Drebot, I.; Gambaccini, M.; Giannotti, D.; Loria, A.; et al.
Highlights: Dual-energy and K-edge subtraction imaging. Rotational radiotherapy of breast cancer. Phase-contrast imaging with coherence areas of about 10  μ m. Abstract: MariX is a research infrastructure conceived for multi-disciplinary studies, based on a cutting-edge system of combined electron accelerators at the forefront of the world-wide scenario of X-ray sources. The generation of X-rays over a large photon energy range will be enabled by two unique X-ray sources: a Free Electron Laser and an inverse Compton source, called BriXS (Bright compact X-ray Source). The X-ray beam provided by BriXS is expected to have an average energy tunable in the range 20–180 keV and intensities between 10 11 and 10 13 photon/s within a relative bandwidth Δ E / E = 1 –10 % . These characteristics, together with a very small source size ( ~ 20  μ m) and a good transverse coherence, will enable a wide range of applications in the bio-medical field. An additional unique feature of BriXS will be the possibility to make a quick switch of the X-ray energy between two values for dual-energy and K-edge subtraction imaging. In this paper, the expected characteristics of BriXS will be presented, with a particular focus on the features of interest to its possible medical applications.